ENT 530 Business Model Canvas: Feqa Studio / Abang Iffat Syahmi Abang Djohan ... [et al.] - Abang Djohan, Abang Iffat Syahmi; Abdullah, Afandi Aqmal; Abdul Jamil, Afrina Rauhah; Noordin, Mohd Norakmaal Hakimi; Ruzi, Muhammad Syafiq; Noor Alamshah, Nur Atirah Zahrah; Allhadi, Nur Nillam Sari; Mohd Rafiz, Sarah Jasmin (2021)
During the early stages of the pandemic that is currently affecting the world, Miss Afeqa Dahan had to quit her job at Hilman.co due to the cut on her wage and the lack of transportation. For this reason, she was forced to find other means to make ends meet. Miss Afeqa adores art and is rather skillful in fashion which is how she was inspired to start the business. Initially, she owns an Instagram account where she posted her paintings and artworks. She has always been fond of influencing people with her fashion, so in January 2021, she used this skill to turn her account into a business account that sells surprise boxes that will satisfy every customers’ unique preferences. As she started gaining attention and customers, she made it her mission to spread happiness using her artistic service and to bring a smile to others faces with surprise. A couple of months after the business began accepting orders, while also helping her persevere through the pandemic, her business gains attention and starts to prosper among young adults in Malaysia. This is especially true for female audiences and is hugely influenced and thanks to the online phone application, TikTok and soon it is possible for this to be her main income. This assessment is to study the Business Model Canvas of Feqa Studio. The first chapter introduces the company and the problem that they are facing as well as the opportunity of recognition. Other than that, there is the evaluation of Feqa Studio Business Model Canvas using SWOT analysis and the purpose. Chapter two of the report goes to the in-depth explanation of the company’s improved business proposal. This report will end with the conclusion and some suggestions that Feqa Studio can follow to further grow their business.